“Comment” As A Development Of Marine Tourism And Flood Disaster Management Based On Go Green At Blendung Beach - Mohammad Nur Khaqiqi; Luqman Haqiqi Amirulloh (Islamic Studies Journal for Social Transformation, 2021)
The phenomenon of tidal waves in coastal areas is a common thing. The Keramat Sari beach is no exception(people are familiar with Blendung beach) which is located in Blendung Village, Ulujami District, PemalangRegency. Around the Pantura, almost every year there are high and low tidal floods. This tidal flood even enteredthe houses of the residents. Rob at Blendung Beach has occurred since April until now (November), and reachedthe highest rob reaching an adult's foot on June 3, 2020. This tidal flood has greatly impacted the sustainabilityof Blendung Beach tourism in terms of the economy of the residents who manage and sell on Blendung Beach.Moreover, with the Covid-19 pandemic, which has made the economy decline so that the problem is even morecomplicated. Therefore, the author offers an idea in the form of "COMMENT" as an effort to empower thecommunity to develop marine tourism and flood disaster management based on Go Green in Blendung Beach.COMMENT offers five excellent programs called the 5 Pillars of the COMMENT Program. The five pillarsof the program include (1) a program reforestation (planting trees); (2) the movement of throwing garbage in itsplace; (3) clean living culture program; (4) recycle (recycling waste); and (5) a CD (principled managementtraining programCommunity Development). COMMENT aims to develop marine tourism and flood disastermanagement at Blendung Beach. Through this program, it is expected to improve the quality and competitivenessof Blendung Beach tourism to attract tourists so that later the village economy can grow and develop where it canmeet sustainable economic growth. This scientific article uses a descriptive qualitative method with an approachAsset, Based, Community, and Development (ABCD)